The Significance of Folk Educations in the Works of Abdulla Aripov - Khamdamov, Akram Nasriddinovich (European Journal of Life Safety and Stability (2660-9630), 2022)
This scientific article is devoted to the study of one of the aspects of the creative activity of the national poet of Uzbekistan Abdulla Aripov, namely, the analysis of the influence of various genres of folklore on his work. The author of the article analyzes and notes that based on folklore images, folk parables and legends, the wisest philosophical and didactic thoughts, the poet reflects on the most important philosophical and artistic problems of various spheres of life and society. So, analyzing the influence of folk legends when creating the poem "The Old Well", the poet, in the opinion of the author of the article, makes important philosophical judgments: "Not every truth needs to be said." According to the author of the article, in the poem "Sick and Doctor", the poet seeks to express one of the main ideas of Sufism: "Being alive, not to be", "to die without dying", "cease to exist", which is one of the leading motifs of classical oriental literature. In general, this article analyzes the harmonious unity of artistic and visual poetic design with various genres of folklore.